2007
DOI: 10.3357/asem.2119.2007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Levels in Rats Following Exposure to Oxygen at 3 atm for 0–120 min

Abstract: The results of this study exhibited a clear relationship of HBO-induced oxidative action to exposure time. This action was most pronounced from 90 to 120 min of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Almost all of our previous one-session HBO exposure studies also resulted in increased SOD activities in rat erythrocytes (9,11,14). Similarly, we recorded significant elevation of SOD activities in the present work, but only in the early 5 and 10 times HBO administered groups.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Almost all of our previous one-session HBO exposure studies also resulted in increased SOD activities in rat erythrocytes (9,11,14). Similarly, we recorded significant elevation of SOD activities in the present work, but only in the early 5 and 10 times HBO administered groups.…”
Section: Discussionsupporting
confidence: 65%
“…Through the last decade, our laboratory has been concentrated on defining the oxidative action of HBO within therapeutically applied limits. In a series of experimental studies conducted in rats, we found that HBO-induced oxidative stress is directly proportional to the exposure pressure (9, 10) and duration (11,12). Another experimental set revealed an important finding that the enhanced levels of oxidation products declined to their baseline values at one hour later following a single HBO exposure (13,14).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…One study assessing oxidative stress levels in rats following exposure to oxygen at 3 atm for 0-120 minutes exhibited a clear relationship of HBO-induced oxidative action to exposure time. This action was most pronounced from 90 to 120 minutes of exposure [29]. Another study on the effects of HBO in rats revealed that after 2 hours of HBO exposure at 3 ATA, levels of the oxidative stress markers elevated in lung, brain and erythrocytes [30].…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated an increase in antioxidant capacity following treatment. Hyperbaric exposure has been shown to cause an increase in oxidative stress in both animal and human experiments (Bearden et al 1999;Otler et al 2007;Benedetti et al 2004), however diVerences in subject population (healthy or diseased), methodology (speciWcally sample type, i.e. tissue, erythrocytes or serum/plasma) and sample timing has an inXuence on the outcome.…”
Section: Discussionmentioning
confidence: 98%